1994
DOI: 10.1128/iai.62.12.5505-5510.1994
|View full text |Cite
|
Sign up to set email alerts
|

Moderate stress protects female mice against bacterial infection of the bladder by eliciting uroepithelial shedding

Abstract: We have previously shown (M. Aronson, O. Medalia, D. Amichay, and O. Nativ, Infect. Immun. 56:1615-1617, 1988) that shedding of viable uroepithelial cells (elicited by invading microorganisms) constitutes an antimicrobial defense mechanism. The present study deals with two different stress-involving procedures, in which increased uroepithelial shedding rendered female mice resistant to vesical infection. Moderate stress was induced in female mice by exposing the animals either to constant illumination for 96 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…faecalis harbored within the urothelial cells of chronic UTI patients 55 . This previous report also slowed sloughing of umbrella cells from the epithelial lining into the urine, which is known in both mice and humans to be a common response to infection 67 71 . These findings were echoed in our urothelial organoid, where E .…”
Section: Discussionmentioning
confidence: 52%
“…faecalis harbored within the urothelial cells of chronic UTI patients 55 . This previous report also slowed sloughing of umbrella cells from the epithelial lining into the urine, which is known in both mice and humans to be a common response to infection 67 71 . These findings were echoed in our urothelial organoid, where E .…”
Section: Discussionmentioning
confidence: 52%
“…Several authors have demonstrated rapid desquamation of urothelial cells following induction of a variety of stress syndromes (Dalal et al. ; Jezernik et al. ; Veramic and Jezernik ; Apodaca et al.…”
Section: Discussionmentioning
confidence: 99%
“…noted patchy areas of urothelial desquamation (single or multiple umbrella cells) and dilatation of extra cellular spaces (if urine was in the bladder) following 96 h constant environmental illumination, or single‐intraperitoneal injection of stress hormones (norepinephrine and hydrocortisone) in mice (Dalal et al. ; Jezernik et al. ; Veramic and Jezernik ).…”
Section: Discussionmentioning
confidence: 99%
“…Acute and chronic stress due to abuse can alter these circuits, their neurochemical components, and bladder function [24,25]. In animal models stress changes bladder histology en physiology [26][27][28][29][30]. Link et al also mentions a role for corticotrophin-releasing factor (CRF), a primary neurotransmitter expressed by neurons within the central stress network [3].…”
Section: Discussionmentioning
confidence: 99%